بحث كتاب "حجة الصديق لدفع الزنديق" للشيخ نور الدين الرانيري (JOURNAL OF INDONESIAN ISLAM, 2009)
This paper is aimed at explicating the Sufistic idea of Sheikh Nur al-Din al-Raniri, a scholar from Aceh through a critical investigation of his Hujjat al-Siddiq li Daf` al-Zindiq (the Argument of the Truthful against the Apostate) and, to a lesser extent, his Himmat al-`Ulama’ `ala Ri`ayah (the Commitment of the Religious Scholars over their Subject). The latter serves as the intellectual and theoretical ground for the former. The paper argues that his many works are all aimed at not only disseminating mystical knowledge, but also at constructing sufi-based culture and tradition in Aceh. For al-Raniri, the paper further argues, faith is the basis of a society. Hence, al-Raniri’s conception of faith and how this central concept is related in his understanding to the process of society-building deserve a careful analysis.